A novel scheme for enhanced content integrity, authentication, and privacy in information centric network using lightweight blockchain-based homomorphic integrity and authentication - Chandra, Aravinda Thejas; Shivarudraiah, Rajashekara Murthy; Gadde, Nagaraja; Nagarajappa, Ravi Kumar Begur (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Information-centric networks (ICNs) face challenges in ensuring content integrity and authentication while preserving user privacy. Homomorphic encryption has been widely used to protect content privacy within ICNs. Blockchain technology is widely applied in ICNs to ensure content integrity. Conventional blockchain-based authentication schemes rely on computationally expensive homomorphic encryption to perform secure data transmission. Also, the existing cryptography methods comprise confidentiality, and integrity while sharing content in ICNs. This paper proposes a novel lightweight blockchain-based homomorphic integrity and authentication (Light-BHIA) scheme to increase the integrity and privacy of content within ICNs. This scheme leverages the transparency and immutability of blockchain, the privacy-preserving properties of homomorphic encryption, and decentralized trust mechanisms to achieve secure and verifiable content delivery. The proposed work utilizes a lightweight homomorphic encryption scheme specifically designed for ICNs, reducing computational burdens by using resource-constrained devices. Light-BHIA uses the permissioned blockchain with an efficient consensus mechanism for increasing the trustworthiness of content delivery within ICNs. Authorized recipients can perform integrity and authentication checks on the encrypted content without decryption, maintaining confidentiality. The comparative study reveals proposed scheme achieved a 25% reduction in registration delay and confirms higher integrity, privacy, and confidentiality.